Unresolved Coronary artery aneurysms in an adolescent with multisystemic inflammatory syndrome in children associated with SARS-CoV-2 infection- What happens in the long term?- Case report - Govardhan, Chaitra; Ragavaiah Naidu, Poornima; D’Souza, Fulton (International Journal of Contemporary Pediatrics, 2025)
MIS-C, a well-known association with SARS-CoV-2 infection, has been a topic of significant interest. It presents with Kawasaki-like illness along with coronary artery dilation or aneurysms. In this report, we describe a particularly intriguing case of an adolescent with MIS-C presenting with coronary artery aneurysms persisting at the end of a 6-month follow-up, underscoring the importance of this condition. An 11-years-old adolescent female presented with fever, livedoid vasculitis rash over lower limbs, abdominal pain and breathlessness. Diagnosis of MIS-C was established based on the clinical findings, elevated inflammatory markers and positive SARS-CoV-2 IgG antibodies. Echocardiogram evidenced myocardial dysfunction with moderate pericardial effusion and coronary aneurysm. She was treated with intravenous immunoglobulins, steroids and aspirin. Serial follow-up until 6 months showed persisting skin changes and coronary aneurysms with normalized inflammatory markers. MIS-C and its related long-term outcome have been well recognized; however, longer follow-up is not just essential, but urgent in understanding this known yet novel condition.